ANALISIS TINGKAT KESENJANGAN ANTARA HARAPAN DAN KENYATAAN KUALITAS PELAYANAN PADA NASABAH BANK KB BUKOPIN PASCA AKUISISI - Wijayanti Nugraeni; Sri Murtiasih (STKIP Persada Khatulistiwa Sintang, 2026)
Business acquisitions in the banking industry aim to expand markets, strengthen capital structures, and enhance institutional competitiveness. However, structural changes resulting from acquisitions often impact customer perceptions and satisfaction with the services provided. In this context, it is important to evaluate how the quality of post-acquisition services is received by customers, particularly in the case of Bank KB Bukopin, which has officially merged with KB Kookmin Bank from South Korea. This study aims to analyze customer perceptions of the quality of Bank KB Bukopin's services after the acquisition process, using the SERVQUAL approach, which covers five main dimensions, namely Tangibles, Reliability, Responsiveness, Assurance, and Empathy. This research is quantitative in nature, with data collected through questionnaires distributed to Bank KB Bukopin customers. The analysis was conducted using the GAP Analysis method to determine the difference between customer expectations and the actual perceived service performance. Furthermore, the analysis results were mapped into a Cartesian Diagram to identify service improvement priorities. The results showed that several indicators were still below customer expectations, especially in the dimension of responsiveness. Therefore, KB Bukopin Bank needs to focus primarily on improving service speed, complaint handling effectiveness, and more efficient communication. These findings are expected to form the basis for a service quality improvement strategy that is more targeted and relevant to the dynamic needs of customers.